2019
DOI: 10.1101/708685
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Describing the fecal metabolome in cryogenically collected samples from healthy participants

Abstract: Introduction:The chemical composition of feces plays an important role in human metabolism. Metabolomics and lipidomics are valuable tools for screening the metabolite composition in feces. Here we set out to describe fecal metabolite composition in healthy participants in frozen stools.Methods: Frozen stool samples were collected from 10 healthy volunteers and cryogenically drilled in four areas along the specimen. Polar metabolites were analyzed using derivatization followed by two-dimensional gas chromatogr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Galactonic acid (the main component of pectin) was positively associated with Christensenellaceae in this study, suggesting that Christensenellaceae may be useful in degrading dietary polysaccharides. Moreover, 3phenyllactic acid has antimicrobial properties and is related to phenylalanine metabolism, and phenylalanine can be catalyzed by phenylalanine hydroxylase to produce tyrosine (Yang et al, 2018;Trost et al, 2020). Our results suggest that Prevotellaceae and Bacteroidales exert positive and negative effects on the tyrosine metabolic pathway, respectively.…”
Section: Discussionmentioning
confidence: 74%
“…Galactonic acid (the main component of pectin) was positively associated with Christensenellaceae in this study, suggesting that Christensenellaceae may be useful in degrading dietary polysaccharides. Moreover, 3phenyllactic acid has antimicrobial properties and is related to phenylalanine metabolism, and phenylalanine can be catalyzed by phenylalanine hydroxylase to produce tyrosine (Yang et al, 2018;Trost et al, 2020). Our results suggest that Prevotellaceae and Bacteroidales exert positive and negative effects on the tyrosine metabolic pathway, respectively.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, the digestion of SM being slow and incomplete, it may induce an important increase of non-digested SM and non-absorbed Cer in the lumen content (3,30), which may explain the present results. Moreover, fecal metabolites, including the various lipid species normally found in feces, may originate directly from food, but also from host cells, bacterial cell components or indirectly from the molecular conversion of SP by gut microorganisms or host enzymes (37). In a recent study performed in healthy patients, plasma and fecal lipidomic analyses demonstrated that the lipid fraction of fecal samples contains significant amounts of Cer species with only two SM species detected, while plasma samples commonly contain significant amounts of several SM species and lower quantities of Cer (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, fecal metabolites, including the various lipid species normally found in feces, may originate directly from food, but also from host cells, bacterial cell components or indirectly from the molecular conversion of SP by gut microorganisms or host enzymes (37). In a recent study performed in healthy patients, plasma and fecal lipidomic analyses demonstrated that the lipid fraction of fecal samples contains significant amounts of Cer species with only two SM species detected, while plasma samples commonly contain significant amounts of several SM species and lower quantities of Cer (37,38). Herein, we chose to determine the concentration of In ileostomy patients, we report higher total SM amount in ileal content compared to total Cer, while total Cer was largely more abundant in the fecal samples compared to total SM.…”
Section: Discussionmentioning
confidence: 99%
“…For the healthy and ALD cohorts, participant recruitment protocol including inclusion and exclusion criteria, setting and locations where data were collected can be found in the original report (Thiele et al, 2016;Thiele et al, 2018;Trošt et al, 2020). The same applies for sample-and clinical data collection procedure, detailed description of the cohort characteristics and anything related to the original clinical study design.…”
Section: Participant Recruitment and Clinical Data Collectionmentioning
confidence: 99%